Impact of Moringa oleifera Cake Residue Application on Waste Water Treatment: A Case Study - Ali, Eman N.; Tan, C. S.; Makky, Essam A. (Scientific Research Publishing Inc., 2014)
Most of water treatments require higher expenditure. Chemical coagulant requires higher cost and has some drawback after treatment such as pH changes. Moringa oleifera cake residue (MOCR) is one of the alternatives to replace chemical coagulant. A jar test apparatus was used to monitor water treatment. Water quality of Gebeng River (GR) and waste water (WW) was examined before and after treatment. Different parameters using (MOCR) was investigated. Preliminary laboratory results showed the great potential of the (MOCR) to be used in water treatment. MOCR shows an excellent reduction in turbidity (97 % was removed). The bacteria were reduced from 1.7 × 10 to 8 × 10 CFU/ml. Dissolved oxygen (DO) was improved that elevated from 1.06 ± 0.04 to 5.09 ± 0.03 mg/L. However, chemical oxygen demand (COD) and biological oxygen demand (BOD) were increased from 520.5 ± 0.71 to 865.0 ± 2.12 mg/L and from 120.5 ± 2.12 to 270.5 ± 2.12 mg/L respectively. Nevertheless, there is no significant alteration of pH, conductivity, salinity and total dissolved solid (TDS) after treatment. The iron (Fe) was fully removed while copper (Cu) and cadmium (Cd) were successfully removed up to 98%. The reduction of lead (Pb) also achieved 82.17%. Also, (MOCR) can be stored for long time up to 6 months without affecting the biological properties of MO.